Time’s up: the urgency to investigate time toxicity in patients with genitourinary malignancies - Daniel Sentana-Lledo; Alicia K. Morgans (Therapeutic Advances in Medical Oncology)
Patients with genitourinary (GU) malignancies have seen the development of multiple life-prolonging treatments in the past decade. As patients and clinicians consider their treatment options along the cancer journey, time spent with healthcare contact, or “time toxicity,” has emerged as a new outcome measure that comprehensively considers time receiving cancer care, including planned visits for evaluation and treatment as well as unplanned urgent care addressing complications. Despite its rising study across cancer populations, there has been a surprising lack of work evaluating time toxicity in patients with GU cancers. This narrative review aims to summarize the available studies on time toxicity in cancer, with a deeper dive into the methodology, strengths and limitations, and future directions of the field. A dedicated section focused on scenarios and best practices to measure and collect data on time toxicity can serve to spark interest in evaluating this novel health outcome on GU cancer survivors. Ultimately, time toxicity is a relevant patient-centered metric that can be incorporated into clinical trial design and routine clinical care to influence clinical decision-making.